Influencia del uso de las técnicas de estudio en el rendimiento académico en los estudiantes del instituto particular “Misael Acosta Solís” del segundo, cuarto y sexto nivel, (modalidad presencial) del cantón Riobamba, de la provincia de Chimborazo; durante el periodo académico marzo – julio 2015 - Cárdenas Villarroel, Rosa Yesenia (2017)
The present research work entitled: "Influence of the use of study techniques in the academic performance in students of the" Misael Acosta Solís "Private Institute of the second, fourth and sixth level (present modality) of the cantón Riobamba, in the province of Chimborazo; during the academic period March - July 2015 ". Its main objective is to investigate how the techniques of study influence the academic performance of the students to investigate. The content focuses on the variables that contain topics and subtopics that refer to the study techniques used by students of second, fourth and sixth level to improve academic performance. The research process was based on a non-experimental design, the types of research focused on a field work, descriptive, exploratory, quantitative, qualitative; The methods applied were the inductive - deductive, synthetic analytic focused on general facts to reach the individuals, applied in a sample of 47 students. Finally, an observation sheet from which statistical data were obtained with the analysis and interpretation of results in order to reach the conclusions and recommendations of the investigation.